Sustaining Competitive Excellence in the Age of Artificial Intelligence - Boulano, Zayeb; Maouri, Hasan; Babayako, Alex (Journal of Current Research In Multidisciplinary, 2026)
The rapid emergence of artificial intelligence has fundamentally altered the global business landscape, forcing organizations to rethink their traditional competitive strategies. This study explores the mechanisms through which companies can maintain a long-term advantage by integrating AI into their core operations and decision-making processes. Through a qualitative analysis of industry leaders, the research identifies that excellence is no longer derived solely from static resources but from the ability to harness predictive analytics and machine learning. The findings suggest that a hybrid approach, combining human intuition with algorithmic precision, creates a unique value proposition that is difficult for competitors to replicate. Ultimately, this paper highlights the necessity of cultural readiness and ethical frameworks in ensuring that AI adoption leads to sustainable growth rather than short-term gains. It serves as a strategic roadmap for firms aiming to navigate the complexities of the digital-first economy,